IMPLEMENTASI STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS DI SLB NEGERI TENGGARONG - Maryam; Ramadhan, M. Tegar; Abror, Muhammad; Hidayat, M. Nabil Wahyu; Hidayat, Muhammad Azis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of Islamic Religious Education teachers’ strategies in inclusive learning for children with special needs at SLB Negeri Tenggarong. The background of this study is based on the importance of applying appropriate learning strategies according to the characteristics of children with special needs so that the learning process can run effectively. This study used a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, simple interviews, and documentation during the learning process. The results showed that Islamic Religious Education teachers implemented several learning strategies, such as the use of visual media in the form of projectors and PowerPoint (PPT), repetition of learning materials, and direct practice methods in learning activities. These strategies helped students understand the material more easily. In the learning process, teachers also used individual approaches and simple communication to build interaction with students. However, several obstacles were found, such as the low response of students in interacting and the difficulty of teachers in creating a more active classroom atmosphere. Therefore, it is necessary to develop more creative and interactive learning strategies so that inclusive learning can run optimally for children with special needs.